2016
DOI: 10.1002/jcb.25536
|View full text |Cite
|
Sign up to set email alerts
|

Airway Hyperresponsiveness in Asthma Model Occurs Independently of Secretion of β1 Integrins in Airway Wall and Focal Adhesions Proteins Down Regulation

Abstract: The extracellular domains of some membrane proteins can be shed from the cell. A similar phenomenon occurs with β1 integrins (α1β1 and α2β1) in guinea pig. The putative role of β1 integrin subunit alterations due to shedding in airway smooth muscle (ASM) in an allergic asthma model was evaluated. Guinea pigs were sensitized and challenged with antigen. Antigenic challenges induced bronchoobstruction and hyperresponsiveness at the third antigenic challenge. Immunohistochemistry and immunoelectronmicroscopy stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…ITGB1 encodes an integrin beta subunit that functions as receptor for fibronectin; along with the increased expression of fibronectin, this would result in enhanced functional consequences for the airway. Interestingly, a recent study in a guinea pig model found that ITGB1 expression was increased in asthma 57 . Vinculin ( VCL ), that has a role in regulating cell–matrix adhesion, including the assembly, turnover, and strength of focal adhesions, as well as the transmission of force by these cellular structures, was downregulated in myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…ITGB1 encodes an integrin beta subunit that functions as receptor for fibronectin; along with the increased expression of fibronectin, this would result in enhanced functional consequences for the airway. Interestingly, a recent study in a guinea pig model found that ITGB1 expression was increased in asthma 57 . Vinculin ( VCL ), that has a role in regulating cell–matrix adhesion, including the assembly, turnover, and strength of focal adhesions, as well as the transmission of force by these cellular structures, was downregulated in myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The myofilament-localized ILK isoform contains a series of ankyrin regions similar to those in the PP1c subunit of MLCP, and this isoform may interact with MLC20 (Lynch et al, 1999). However, its role in hypercontractility and hyperresponsiveness is unclear, because ILK expression has been demonstrated to be reduced in experimental asthma (Álvarez-Santos et al, 2016).…”
Section: Integrin-linked Kinase (Ilk) As Regulator Of Mlcp In Airway mentioning
confidence: 99%
“…In cultured A7r5 rat embryonic aorta smooth muscle cells, ROCK-mediated phosphorylation of MYPT1 at Thr 695 is similar to that of phosphorylation of human MYPT1 at Thr 696 , and phosphorylation of rat MYPT1 at Thr 850 is similar to that of phosphorylation of human MYPT1 at Thr 853 ( Murányi et al, 2005 ). In a guinea pig model of asthma and in airway smooth muscle from asthma patients, increased phosphorylation of MYPT1 occurs at Thr 696 ( Álvarez-Santos et al, 2016 ; Yoo et al, 2017 ). In addition, phosphorylation of MYPT1 at Thr 696 by ROCK in bovine airway smooth muscle inhibits MLCP activity, although Thr 853 phosphorylation does not alter its phosphatase activity ( Gao et al, 2017 ).…”
Section: Rho-associated Kinase (Rock) Is a Key Regulator Of Airway Smmentioning
confidence: 99%